The hidden relation between Chairman and CEO compensation - Camelo, A.; Esperança, J. (PFN 2012 Conference, 2012)
Shareholders rely on the board of directors to protect their interests, including the setting of efficient management compensation packages. The chairman plays a key role to ensure the appropriate monitoring and control by the board of directors. Although often acknowledged in the literature, the link between the board of directors and compensation has been neglected by empirical research. This study is focussed on the impact of chairman characteristics on CEO compensation, using a sample of 688 large listed corporations, from different countries and regions. Our results provide strong evidence that chairman characteristics do influence CEO compensation.